An Extension of the Bierman-Hausman Model for Credit Granting - Dirickx, Yvo M. I.; Wakeman, Lee (Management Science, 1976)
This paper extends the Bierman-Hausman credit-granting model by proving that although the distribution on the probability of collection in the case of failure is no longer a conjugate Beta, it remains tractable; the model therefore need no longer be terminated in the case of failure. Further theorems on the structure of optimal policies, which result in a considerable reduction of the dynamic programming state space, are then presented, and the paper concludes with a discussion of extensions and applications.